140 In vivo depletion of endoglin results in significant left ventricular remodelling. (9th June 2011) - Davison, B J; Redgrave, R; Keavney, B; Blamire, A; Arthur, H
Abstract : Endoglin, a TGFβ co-receptor, is essential for cardiovascular development. However, endoglin also has an important role in fibrosis in adult life. Endoglin heterozygous mice have been shown to have reduced fibrosis in response to renal injury. They also have significantly reduced cardiac function following myocardial infarction. In rat cardiac fibroblasts, endoglin expression is up regulated following stimulation with angiotensin II and TGFβ, resulting in reduced expression of MMP1 and increased expression of collagen I. These effects are inhibited by an endoglin specific antibody. Using our conditional endoglin knockout mice we sought to investigate the role of endoglin in cardiac healing following myocardial infarction. Adult Eng fl/fl Rosa26-Cre ERT2 or control (Eng fl/fl) mice were treated with intraperitoneal injection of tamoxifen for 5 days to activate Cre ERT2 and deplete endoglin by Cre-lox recombination. Mice then underwent surgical coronary artery ligation or sham operation. Cine cardiac MRI was performed 28 days after injury. Measurement of left ventricular (LV) volumes and myocardial mass were made using ImageJ, and parameters of cardiac function were calculated. We found that LV volumes and mass were significantly increased (p<0.001) and ejection fraction significantly reduced (p=0.005) in endoglin deficient mice compared to controls. However, we also noticed LV volume and mass were increased in sham operated endoglin deficient mice. This led us to investigate the effect of endoglin knockdown on normal heart structure and function in adult mice. Cine cardiac MRI was therefore performed on mice without any surgical procedure after endoglin knockdown. We found that in the endoglin deficient mice, LV volume and mass were again significantly increased (p<0.03). However, ejection fraction did not differ significantly from controls. These results demonstrate that depletion of endoglin results in significant left ventricular remodelling and suggest that endoglin plays an essential role in the maintenance of normal cardiac structure. The fact that cardiac function was preserved indicates that this is not a cardiomyopathic process and we hypothesise that the increased left ventricular volume in the endoglin-deficient mice may be the result of alterations in the extracellular matrix. We are currently investigating this potential molecular mechanism for left ventricular remodelling in the absence of endoglin.